The world innovation landscape: Asia rising? - Reinhilde Veugelers (Bruegel, 2013)
Highlights - Research and development spending has risen rapidly in Asia, particularly in China, which is now the world's second R&D spender behind the United States.The increase in Korean and Chinese patent applications has been even more rapid, but Chinese patenting for exploitation on the main markets for innovation(the European Union, Japan and the US) is still marginal. - Asia's increased innovation spending is most prominently related to information and communication technologies. Overall, the Chinese and Korean economies are still not specialised in knowledge-intensive goods and services.Furthermore, China in particular is not (so far) capturing much value from its role as a manufacturer and exporter of high-tech goods; China remains mostly an assembler of goods, the value of which is created elsewhere. - It would be wrong to ignore China's innovation potential on the basis of its current performance. Its clear innovation ambitions are likely to drive its future growth. - Europe is struggling much more than the US to retain its place at the global innovation table. The EU should use Asia's capacity building in innovation as an opportunity for value capture.
Keywords: 330